Encryption On Grayscale Image For Digital Image Confidentiality Using Shamir Secret Sharing Scheme. (April 2016) - Rodiah,; Anggraini, Dyah; Fitrianingsih,; Kazhimi, Farizan
Abstract: The use of high-frequency internet in the process of exchanging information and digital transaction is often accompanied by transmitting digital image in the form of raster images. Secret sharing schemes are multiparty protocols that related to the key establishment which provides protection against any threats of losing cryptography key. The greater the key duplication, the higher the risk of losing the key and vice versa. In this study, Secret Sharing Method was used by employing Shamir Threshold Scheme Algorithm on grayscale digital image with the size of 256×256 pixel obtaining 128×128 pixels of shared image with threshold values (4, 8). The result number of shared images were 8 parts and the recovery process can be carried out by at least using 4 shares of the 8 parts. The result of encryption on grayscale image is capable of producing vague shared image ( i.e., no perceptible information), therefore a message in the form of digital image can be kept confidential and secure.